2021
DOI: 10.1108/apjba-04-2021-0175
|View full text |Cite
|
Sign up to set email alerts
|

Internal branding, employees' brand commitment and moderation role of transformational leadership: an empirical study in Indian telecommunication context

Abstract: PurposeThe purpose of this paper is to examine the relationship between internal branding (IB) and employees' brand commitment and analyze how transformational leadership (TFL) moderates this relationship.Design/methodology/approachData were collected through structured questionnaires from 394 employees in Indian telecommunication sector. The hypotheses and conceptual model were tested by structural equation modeling (SEM), using Statistical Package for Social Sciences (SPSS) and Analysis of Moment Structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Thus, the commitment of these employees is purely externally driven. In fact, the previous research showed no significant impact of internal branding on continuance OC (Binu Raj, 2021). Therefore, an uncertain job market with a high unemployment rate, along with temporary and performance-based contracts, can explain these behavior patterns.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Thus, the commitment of these employees is purely externally driven. In fact, the previous research showed no significant impact of internal branding on continuance OC (Binu Raj, 2021). Therefore, an uncertain job market with a high unemployment rate, along with temporary and performance-based contracts, can explain these behavior patterns.…”
Section: Discussionmentioning
confidence: 80%
“…Most research on OC applied a variable-centered approach that emphasizes relationships between these individual commitment mindsets and various drivers or job-related consequences, such as internal branding, trust, satisfaction, well-being, etc. (Allen, 2016;Binu Raj, 2021;Taing et al, 2011)using Statistical Package for Social Sciences (SPSS. Additionally, scholars and practitioners have focused on person-centered analytic techniques that group employees with homogeneous OC types into the same profile (Kam et al, 2016;Meyer et al, 2019;Stanley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“… Jeon and Yoo (2021) also found that customer affective commitment plays a constructive role in strengthening the relationship between product perceived value and customer-based brand equity. Binu Raj (2021) concluded that perceived value significantly impacts customer engagement, and affective commitment and affective commitment facilitate the relationship among the customer of the hotel industry. Similarly, Slack et al (2020) also revealed that brands consider commitment as an internal brand strength that can induce brand equity.…”
Section: Discussionmentioning
confidence: 99%
“…Employee brand internalization guarantees that employees have a thorough understanding of brands and a strong commitment to them, which reflects cognitive and emotive pathways to EBBE ( Maleki Minbashrazgah et al, 2021 ). Employees will encourage pro-brand activities after they acknowledge the organization’s aims and values ( Binu Raj, 2021 ). The more a company’s ideas and principles of service are internalized, the more consistently and successfully employees will execute as a result ( Sonmez Cakir and Adiguzel, 2022 ).…”
Section: Discussionmentioning
confidence: 99%